Optimal sensors positioning to detect forest fire ignitions - Brito, Thadeu (2020)
Forests have been harassed by fire in recent years. Whether by human action or for other reasons, the burned area has increased harming fauna and flora. It is fundamental to detect an ignition early in order to firefighters fight the fire minimizing the fire impacts. The proposed Forest Monitoring System aims at improving the nature monitoring and to enhance the existing surveillance systems. A set of innovative operations is proposed that will allow to identify a forest ignition and also will monitor the fauna. For that, a set of sensors are being developed and placed in the forest to transmit data and identify forest fire ignition. This paper addresses a methodology that identifies the ideal positions to place the developed sensors in order to minimize the fire hazard. Some preliminary results are shown by a random algorithm that spread points to position sensor modules in areas with high risk of fire hazard.